Pendidikan Spiritual dan Religius Mengokohkan Resiliensi Penyalahguna Narkotika di Indonesia - Slamet Fatrika Santoso; Palupi Lindiasari Samputra (Departement of Mathematics Education, 2023)
Resilience for people who abuse drugs is important. Resilience can be built by the presence of spirituality. This paper is a literature review on the benefits of spiritual and religious-based programmes used to address drug misuse in Indonesia. The use of 46 articles published from 2018-2023, from Google Scholar, shows a variety of treatment models for spirituality and religion-based interventions including Sufistic approaches, spiritual counselling, religious guidance, worship, Therapeutic Community (T.C) which has aspects of spiritual care and the 12 steps or Narcotic Anonymous (N.A). The outcomes and goals of spiritual and religious interventions for drug abusers include relapse prevention, increased trust (faith), worship behaviour and productivity, building good social relationships that are in harmony with oneself, and inner well-being that reduces stress and psychological disorders as well as physical disorders, self-control, self-awareness, resilience, having meaning and purpose in life that is in harmony with nature. Spirituality and Religion are part of relapse prevention, building productive behaviour and increasing the faith of drug abusers.